THE VIABILITY OF LOCAL GOVERNMENT INFORMAL SETTLEMENT - MALOKA, J NKOANA (My University, 2011)
The South African local government is under constant criticism for its inability to deliver low cost housing to poor citizens who do not own houses, and who end up living in hazardous environments such as shallow mine dumps. They live in informal settlements that are generally inhabitable for human beings. The purpose of this research is to determine the viability or workability of local government informal settlement upgrading strategy. One of the critical findings, contrary to general perceptions is the effective communication of the strategy with beneficiaries in the municipality. Informal settlement dwellers participated in the strategy formulation from its conception as well as towards implementation. The strategy is comprehensive in “social processes or sociological approach” as well as international and national framework policy thrust, but lags in “micro strategic planning and implementation processes”. The other critical findings are lack of resources, in particular, financial resources; staff capacity; and inter-departmental cooperation. These factors have adverse effect on the informal settlement upgrading strategy. They constitute what would make the strategy not viable or workable. The study proposes review of micro strategic planning and implementation, pursuance of accreditation as well as continuously adaptation to international “slums” or informal settlements improvement strategies and policy imperatives. Accreditation of local authorities is an important vehicle that can enhance speedy implementation of the South African low in-come housing national policy shift dubbed “breaking new ground.”
MM - P&DM
Keywords: Informal settlements; Squatter camps; Local authorities